Ibn Ahmad, Fuad. “Representation and Harshness in Intellectual Debate: Ibn Rushd as a Model,” Year 15, Issue 59 (Winter 1431 AH/ 2010 CE), Pp. 87 - 118. - بن أحمد, فؤاد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2010)
Fuad Ibn Ahmad’s article discusses representation and metaphor in the thought of Ibn Rushd, presenting these as not only epistemological and methodological tools, but as instruments for denigrating the intellectual opponent and debunking their argument by exposing the contradiction between the nature of the opponent and their position. The article addresses the functions of the mechanisms of representation and metaphor and their results, to arrive at a critique of Ibn Rushd. It examines the following themes: al-Ghazālī’s rank among the philosophers; Ibn Rushd’s view of al-Ghazālī; al-Ghazālī and ignorance, evil, and doctrinal instability; al-Juwaynī and the book Al-Kashf; and the mutakalimīn (theologians). The article concludes that Ibn Rushd sometimes used representation as an instrument for criticism and ridicule of his opponents.